Le Sud et la nation américaine au vingtième siècle : espace(s), identité(s), définitions - Anne Stefani (Anglophonia)
The twentieth-century South is a multidimensional space which can be approached from a geographical, historical, or cultural perspective, and which most often takes on a mythical character. Although the region is definitely distinct from the rest of the nation, its identity cannot be defined in a straightforward way, as the abundant literature published on the subject throughout the twentieth century illustrates. The present article revisits the well-known thesis of race as the central theme in Southern culture by extending it to the relationship between the South and the nation. Focusing on the history of North/South relations since the nineteenth century, it shows how and why the South, which once stood as an exception in the nation, has come to symbolize the essence of American identity without losing its distinctiveness.